Protective effect of gastrodin on bile duct ligation-induced hepatic fibrosis in rats. (December 2015) - Zhao, Shuangshuang; Li, Naren; Zhen, Yongzhan; Ge, Maoxu; Li, Yi; Yu, Bin; He, Hongwei; Shao, Rong-guang
Abstract: Gastrodin has been showed to possess many beneficial physiological functions, including protection against inflammation and oxidation and apoptosis. Studies showed inflammation and oxidation play important roles in producing liver damage and initiating hepatic fibrogenesis. However, it has not been reported whether gastrodin has a protective effect against hepatic fibrosis or not. This is first ever made attempts to test gastrodin against liver fibrosis in bile duct ligation (BDL) rats. The aim of the present study is to evaluate the effect of gastrodin on BDL-induced hepatic fibrosis in rats. BDL rats were divided into two groups, BDL alone group, and BDL-gastrodin group treated with gastrodin (5 mg/ml in drinking water). The effects of gastrodin on BDL-induced hepatic injury and fibrosis in rats were estimated by assessing serum, urine, bile and liver tissue biochemistry followed by liver histopathology (using hematoxylin & eosin and sirius red stain) and hydroxyproline content measurement. The results showed that gastrodin treatment significantly reduced collagen content, bile duct proliferation and parenchymal necrosis after BDL. The serum alanine aminotransferase (ALT) and serum aspartate aminotransferase (AST) decreased with gastrodin treatment by 15.1 and 23.6 percent respectively in comparison to BDL group did not receive gastrodin. Gastrodin also significantly increased the level of serum high density lipoprotein (HDL) by 62.5 percent and down-regulated the elevated urine total bilirubin (TBIL) by 56.5 percent, but had no effect on total bile acid (TBA) in serum, bile and liver tissues. The immunohistochemical assay showed gastrodin remarkably reduced the expressions of CD68 and NF-κB in BDL rats. Hepatic SOD levels, depressed by BDL, were also increased by gastrodin by 8.4 percent. In addition, the increases of hepatic MDA and NO levels in BDL rats were attenuated by gastrodin by 31.3 and 38.7 percent separately. Our results indicate that gastrodin significantly attenuated the severity of BDL-induced hepatic injury and fibrosis by attenuating oxidative stress and inflammation. Taken together, these findings suggest that gastrodin might be an effective antifibrotic drug in cholestatic liver disease. Highlights: This is first ever made attempts to test gastrodin against liver fibrosis. Gastrodin significantly attenuated BDL-induced hepatic injury and fibrosis by attenuating oxidative stress and inflammation. Gastrodin might be an effective antifibrotic drug in cholestatic liver disease.